COMPARING CULTURAL PRACTICES AND MAKING SUGGESTIONS FOR EFFECTIVE CROSS-CULTURAL COMMUNICATION - Sotvoldiyeva Mastura Yahyobek qizi; Turaxon Abduraxmonov Saydullayevich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  thesis  explores  the  diversity  of  cultural  practices  across different societies and examines their impact on communication and social interaction. Cultural  practices,  including  traditions,  values, communication  styles, religion, and everyday behaviors, differ significantly between Western and Eastern cultures. The study  provides  a  comparative  analysis  of  these  differences  and  highlights  their influence  on  interpersonal  relationships.  Furthermore,  the  article  identifies  major challenges  in  cross-cultural  communication,  such  as  stereotypes,  ethnocentrism, language barriers, and misinterpretation of non-verbal cues. Special attention is given to the role of globalization in increasing intercultural interactions. The thesis also offers practical recommendations for improving cross-cultural communication,  including  enhancing  cultural  awareness,  developing  empathy, improving  language  skills,  and  promoting  intercultural  education.  The  findings emphasize  that  effective  communication  in  a  multicultural  environment  requires respect, tolerance, and adaptability.